On the computational complexity of the secure state-reconstruction problem - Mao, Yanwen; Mitra, Aritra; Sundaram, Shreyas; Tabuada, Paulo (Automatica (Oxford), 2022)
In this paper, we discuss the computational complexity of reconstructing the state of a linear system from sensor measurements that have been corrupted by an adversary. The first result establishes that the problem is, in general, NP-hard. We then introduce the notion of eigenvalue observability and show that the state can be reconstructed in polynomial time when each eigenvalue is observable by at least 2s+1 sensors and at most s sensors are corrupted by an adversary. However, there is a gap between eigenvalue observability and the possibility of reconstructing the state despite attacks — this gap has been characterized in the literature by the notion of sparse observability. To better understand this, we show that when the A matrix of the linear system has unitary geometric multiplicity, the gap disappears, i.e., eigenvalue observability coincides with sparse observability, and there exists a polynomial time algorithm to reconstruct the state provided the state can be reconstructed.